Vanillin Derivatives Reverse Fusobacterium nucleatum-Induced Proliferation and Migration of Colorectal Cancer Through E-Cadherin/β-Catenin Pathway - Zhou, Zhongkun; Wang, Yiqing; Ji, Rui; Zhang, Dekui; Ma, Chi; Ma, Wantong; Ma, Yunhao; Jiang, Xinrong; Du, Kangjia; Zhang, Rentao; Chen, Peng (Frontiers in Pharmacology, 2022)
Colorectal cancer (CRC) is a common clinical malignant tumor and closely related to intestinal microbiome disorders. Especially, Fusobacterium nucleatum (F. nucleatum) is one of the most prevalent pathogens in CRC. However, its change in CRC patients of Northwest China, an area with a high incidence of gastrointestinal tumors, is unclear and therapeutic strategies targeting F. nucleatum remain unresolved. Here, fecal samples of healthy people and CRC patients were studied using 16S rRNA sequencing to explore microbial community alterations. Additionally, vanillin derivates (IPM711 and IPM712) intervention by co-culture with CRC cells and potential mechanism were investigated. Results showed that intestinal microbial homeostasis gradually dysregulated and the abundance of Fusobacterium was higher in CRC patients. Moreover, IPM711 and IPM712 showed better anti-F. nucleatum activity than vanillin by increasing cell membrane permeability and destroying bacterial integrity. In addition, IPM711 and IPM712 could downregulate the expression of E-cadherin and β-catenin, thus suppressing the migration of HCT116. Collectively, IPM711 and IPM712 have both anti-colorectal cancer and anti-F. nucleatum activities, providing potential natural product drug candidates for microbe-targeted strategies for the treatment of CRC.